Comrade Baron : A Journey through the Vanishing World of the Transylvanian Aristocracy - Scholten, Jaap, 1963- (Book collections on Project MUSE., 2016)
In the darkness of the early morning of 3 March 1949, practically all of the Transylvanian aristocracy were arrested in their beds and loaded into lorries. Under the terror of Gheorghiu-Dej and later Ceau escu the aristocracy led a double life: during the day they worked in quarries, steelworks and carpenters yards; in the evening they secretly gathered and maintained the rituals of an older world. To record this episode of recent history, Jaap Scholten travelled extensively in Romania and Hungary and sought out the few remaining aristocrats who survived communism and met the youngest generation of the once distinguished aristocracy to talk about the restitution of assets and about the future.